More notes on Alfredo Dugès’ names for Mexican reptilian taxa - Flores-Villela, Oscar; Reynoso, Victor Hugo (Zootaxa, 2010)
Alfredo Dugès, considered the father of Mexican herpetology (Smith & Smith 1969) lived in the city of Guanajuato, México, where he formed a cabinet of natural history, today the Museo Alfredo Dugès. During the course of an investigation dealing with his life and contributions we have restudied his collections and contributions to Mexican herpetology. Dugès proposed 41 taxonomic names in herpetology. One of these names was considered a nomen nudum by Smith and Smith (1969), 10 were erected for new genera, two for new subgenera, 24 for new species, and four for new subspecies. Five names — three genera and two species — do not belong to the Mexican fauna (Flores-Villela et al. in prep). Previous comments on A. Dugès’ names have been made by Smith (1968, 1969) and Smith and Smith (1969).